Dynamic characteristic of graphene reinforced axial functionally graded beam using finite element analysis. (2022) - Gantayat, A.K.; Sutar, M.K.; Mohanty, J.R.
Abstract: Since last two decades research in the field of Functionally Graded Material (FGM) has notices a potential increment. Further, reinforcement of graphene nanoparticles in FGM enhances their material properties. Application of the graphene reinforced FGM in the domain of biomedical application, aerospace, defense, marine and sports industries need careful dynamic analysis for their better performance. This paper represents the analysis of graphene nano-particle reinforced functionally graded beam (FGB), with varying concentrations in an Epoxy matrix, along the axial direction of the beam. The beam has been analyzed to find out the dimensionless Natural frequency for its first four modes of vibration using the finite element software package ANSYS, and the results have been compared with previously modelled Carbon Nanotubes (CNT) reinforced axially functionally graded beam results. The comparison indicates satisfactory results with superior parameters which can be implemented for further analysis.